Governing the management and use of pooled microbial genetic resources: lessons from the global crop commons. Issue 1 (18th February 2010) - Halewood, Michael
The paper highlights lessons learned over the last 30 years establishing a governance structure for the global crop commons that are of relevance to current champions of the microbial commons. It argues that the political, legal and biophysical situation in which microbial genetic resources (and their users) are located today is similar to the situation of plant genetic resources in the mid-1990s, before the International Treaty on Plant Genetic Resources was negotiated. Consequently, the paper suggests that it may be useful to look to the model of global network of ex situ plant genetic resources collections as a precedent to follow – even if only loosely – in developing an intergovernmentally endorsed legal substructure and governance framework for the microbial commons.